Poetic Styles in the Works of the Omayyad Poets - Abdulkarim Yakoub; Samar Eskandar (دراسات في اللغة العربيّة وآدابها)
Poetry writing has been characterized by spontaneity and intuition, but this spontaneity was neither pure nor innocent, for the poet had to carefully scheme his poetry, urged by his aspiration to be as elevated as his diction and craft could be, together with the competitive spirit which naturally reigns over poetic genius. The poet, thus, had to pursue means which could allow him achieve mastery over poetic craft without damaging the essence of his creativity. Thus, poetic craft was the method by which poets could produce sublime poetry with sublime standards. Omayyad poets sought new polished styles in which they could enrich their poetry with new imagery, making it superior to other writings. These styles shed light on their distinct perception of poetry as well as the notion of poetic craft itself and their employment of this craft in the service of their poems. Poets have employed several styles to enrich their poems, and they have been inspired by ideas from the weaving craft to support their own art. This led to the incorporation of notions such as weaving, knitting, embellishment, purification and correctedness into poetry, as well as many other techniques which improved poetry. The concern with craft for the improvement of poetry drew attention to its flaws. Poets tried hard to avoid these flaws in order to maintain poetry`s elegance and taste.